(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article discusses the significance of morphology and its role in language. Morphology, stemming from the Greek words "morphe" (form) and "logos" (science or word), constitutes a segment of grammar dedicated to the examination of words within the context of their parts of speech. In essence, morphology scrutinizes the broad meanings and alterations of words.